How Do Waste-Picker Families Endure? Resolving Pains and Managing Support Systems as Close Relationship “Resourcing:” A CGT with Readily Available Data - Diego Mauricio Paucar Villacorta (Grounded Theory Review: An International Journal, 2020)
Public waste-management systems in Latin American cities are defective. However, waste-pickers take advantage of this situation and create small family-based waste- processing units. However, little is known about how these families constantly meet their needs, manage suffering or even overcome poverty. How do they get to survive in such a context? This paper presents the classic grounded theory of resourcing from close relationships, based on a secondary analysis of data produced during 2009-2011 by a grass-roots NGO. The core category of managing support systems explains how a family constantly approaches or wards off towards an ideal work system through anchoring motivations and system adjusting. The resulting actual system, however, creates pains. They have to be resolved through tolerating dependency and negotiating against deviance, which is what finally allows the family to adapt or thrive to changing economic environments.